African biblical studies: unmasking embedded racism and colonialism in biblical studies - Mbuvi, Andrew Mũtũa (t&t clark, 2024)
"Andrew M. Mbuvi makes the case for African biblical studies as a vibrant and important emerging distinct discipline, while also using its postcolonial optic to critique biblical studies for its continued underlying racially and imperialistically motivated tendencies. Mbuvi argues that the emergence of biblical studies as a discipline in the West coincides with, and benefits from, the establishment of the colonial project that included African colonization. At the heart of the colonial project was the Bible, not only as ferried by missionaries to convert "heathens in the distant lands," but as the text used in the justification of the colonial violence. On these grounds, Mbuvi makes the case that non-western approaches continue to be marginalized and struggle to gain currency in the discipline as they are generally judged as "unscholarly" or somehow outside of the narrow criteria of western biblical studies. African Biblical Studies exposes these oppressive and subjugating tendencies as unresolved remnants of a colonial past, advocating and applying methodologies and studies that prioritized readings from the perspective of the marginalized and oppressed. These readings destabilize and undermine the dominant approaches and their ingrained prejudices, both in the biblical text and the interpretive process employed in western biblical studies, by reading from below, with the underprivileged and the marginalized"--